Mechanical Properties of an Eco-friendly Concrete with partial replacement of POC and Rubber - Espinoza, A. (2020)
Concrete plants consume 10 billion tons of natural aggregates annually from quarries and gravel plants for produce concrete, this demand requires exploiting natural resources from mountains and rivers producing an ecological imbalance. One solution is to use Palm Oil Clinker (POC), which is eliminated in large quantities in the dumps and rivers without taking advantage of its puzolanic, binding and resistance properties as an aggregate in the concrete; another alternative is to apply rubber from abandoned and discarded tires as waste in landfills or burned, without taking advantage of its performance of improvement in concrete, increasing its resistance to impact and fatigue. Unable to find joint POC and rubber information, this research studies its influence replacing 2.5% rubber (grained and crushed) with 10%, 12.5% and 15% POC in the fine aggregate on traditional concrete; results indicate that with 12.5% of POC as the ideal percentage, the compressive strength, tensile strength and flexural strength rise between 2.16 - 9.54%, so the concrete obtained has a cost of less than 4.09% and has 3.65% less CO2 emission.